Study on Serum Calcium, Magnesium and Uric acid Levels in Preeclamptic and Healthy Pregnant Women - A Comparative Study (Ibrahim Cardiac Medical Journal, 2023)
Background & Objective: Pre-eclampsia is the most common medical complication of pregnancy associated with increased maternal and infant mortality and morbidity. Various dietary deficiencies or excesses have previously been linked to preeclampsia. Many studies have documented that the changes in the concentration of minerals like calcium, magnesium, and uric acid have a link to the etiopathogenesis of preeclampsia. The present study was undertaken to find the associations of serum calcium, magnesium, and uric acid with preeclampsia.Methods: This cross-sectional comparative study was carried out in the Department of Physiology in collaboration with the Department of Biochemistry, Rajshahi Medical College, Rajshahi over a period of one year between July 2018 to June 2019. Pre-eclamptic and healthy pregnant women aged 18-35 years with single-tone pregnancies having agestational age of 28-32 weeks were the study population. While preeclamptic pregnant women were included as cases, healthy pregnant women were included as controls. A total of 100 cases (pre-eclamptic women) and an equalnumber of controls (healthy pregnant women) were included. Serum calcium, magnesium, and uric acid levels of the subjects were compared between the case and the control groups to evaluate their association with preeclampsia.Result: The findings of the study revealed that cases were older and heavier than the controls. However, both groups were alike in terms of gestational age. Both systolic and diastolic blood pressures were much higher in the case group than those in the control group. The serum calcium was significantly decreased in the case group than that in the control group (p < 0.001). The serum magnesium was also significantly dropped in the case group compared to the control group (p < 0.001). However, the serum uric acid was dramatically raised in the former group than that in the latter group (p < 0.001).Conclusion: The study concluded that serum calcium and magnesium levels are significantly decreased and serum uricacid levels significantly increased in preeclamptic women.Ibrahim Card Med J 2022; 12 (2): 27-31